The Oldest Elements of the Serbian Statehood - Đekić, Đorđe N. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Starting from the Constantine VII Porphyrogenitus's work De Administrando Imperio, where he said that after the death of a Serbian archon, the rule over the people was shared between his two sons, it is assumed that the Serbs were then a nomadic, animal herding people, not farmers, so that they lacked a territory as the third element of statehood. The assumption is backed by the fact that a mythical Serbian ancestor was a wolf, which was possible only if they were animal herders and not farmers. From their ancient homeland to Thessaloniki, Serbs covered a vast distance, which was also possible only if they were nomads. Since they did not like the lands around Thessaloniki, they came all the way to Belgrade, a distance of more than 600 kilometres, which was also possible only if they were a nomadic people and not farmers. Granted by Heraclius, the Serbs settled in the western Balkans and as they could not continue their nomadic way of life due to the geography of the region, they had to settle there permanently, which made them turn to farming. This way, the Serbian states obtained the third element of statehood – a territory. Furthermore, by the mid-9th century, the state ceased to be divided by the number of sons, and one son was now a supreme ruler, whilst the others were his subjects. A principle of the second-born was established.
Keywords: second-born principle; territory as an element of statehood; wolf cult; animal herding; immigration of Serbis